EVALUATING GLOBAL MUNICIPAL SOLID WASTE MANAGEMENT EFFICIENCY FROM A CIRCULAR ECONOMY POINT OF VIEW - Rada, Elena Cristina; TOLKOU, ATHANASIA; KATSOYIANNIS, IOANNIS; MAGARIL, ELENA; Kiselev, Andrey; Conti, Fabio; Schiavon, Marco; Torretta, Vincenzo (WIT Transactions on Ecology and the Environment, 2021)
The Circular Economy (CE) principles recently set out by the European Union (EU) include additional guidelines for municipal solid waste (MSW) management. More detailed information about material streams must be generated and managed so that the entire system can be monitored from a new perspective. Suitable indicators (and indices from them) must be made readily available, so that they can be used to assess the efficiency that the European Union expects from the sector. This article presents a preliminary critical analysis of the literature and identifies that indicators and indices should be considered to facilitate the evaluation of MSW management under a CE vision. The analysis is combined with a discussion of the situation in various countries, to provide an overview of attempts to implement CE strategies worldwide. Special waste is not dealt with in this article as EU updated the vision of waste management starting from the MSW sector, on which this work is focused.